Practical clinical guidelines and pharmacological treatment for attention‐deficit hyperactivity disorder in Asia - Kentaro Kawabe; Fumie Horiuchi; Yu Matsumoto; Saori Inoue; Maya Okazawa; Rie Hosokawa; Kiwamu Nakachi; Junya Soga; Shu‐Ichi Ueno (Wiley, 2024)
Abstract Attention‐deficit hyperactivity disorder (ADHD) is characterized by persistent symptoms of inattention, hyperactivity, and impulsivity. Both, stimulant and nonstimulant medications have been approved for the treatment of this disorder. Several Western guidelines recommend the use of prescribed Food and Drug Administration (FDA)‐approved medications for ADHD along with parental training in behavior management and behavioral classroom intervention. In 2022, new Japanese guidelines for ADHD were issued, which recommended school environment management and psychosocial treatment as the first‐line treatment, with pharmacological treatment added as the second‐line treatment. Although Japanese guidelines, including pharmacological treatments, have been established, the guidelines and utilization of ADHD medications across Asian regions are unclear. Therefore, to appropriately evaluate the strategy of pharmacological treatments for ADHD, we investigated Asian regional guidelines for ADHD medication in children. We also reviewed the guidelines in Malaysia, Singapore, India, and the Republic of Korea and found that these guidelines differ from Western guidelines.